Antes que todo = Before Everything. - Aguirre, Peio; Arriola, Aimar; Moscoso, Manuela; Van Loo, Sofie (Madrid : CA2M Centro de Arte Dos de Mayo Madrid, 2010)
Aballi, Ignasi ; Alfaro, Lorea ; Badiola, Txomin ; Ballester Moreno, Antonio ; Beltrán, Erick ; Bestué, David ; Vives, Marc ; Bianchi, Rafel G. ; Congost, Carles ; Crespo, June ; Discoteca Flaming Star ; Esquivias, Patricia ; Euba, Jon Mikel ; Ferrer, Esther ; Fuster, Nuria ; Garcia, Dora ; Garcia, Fernando ; Grilo, Rubén ; Hartmann, Lilli ; Jacoby, Daniel ; Jeleton ; Jimenez Landa, Fermin ; Julià, Adrià ; K.S., Dai ; Kuselman, Tamara ; Llaria, Daniel ; Maneros Zabala, Erlea ; Marte, Pablo ; Meana, Fran ; Mendizabal, Asier ; Mitja, Jordi ; Momu & No Es ; Montilla, Julia ; Okariz, Itziar ; Ortega, Antonio ; Pérez Agirregoikoa, Juan ; Pérez, Kiko ; Pericàs, Gabriel ; Polo, Paloma ; Prego, Sergio ; Prieto, Wilfredo ; Recarens, Tere ; Red Caballo ; Reynolds, Alex ; Ribas, Xavier ; Rodriguez-Méndez, Carlos ; Ruiz, Francesc ; Salaberria, Xabier ; Satorre, Jorge ; Soto, Javi ; Spinola, Julia ; Polaroiska, Sra. ; Urrutia, Alain ; Valcárel Medina, Isidoro ; Vieites, Azucena ; Vilanova, Oriol ; WeareQQ
Before Everything, CA2M Centro de Arte Dos de Mayo, Madri, 2010-09-18. 2011-01-09
boek